Knowledge, information, and creativity support systems 5th International Conference, KICSS 2010, Chiang Mai, Thailand, November 25-27, 2010, revised selected papers (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International Conference on Knowledge, Information, and Creativity Support Systems, KCIS 2010, held in Chang Mai, Thailand, in November 2010. The 23 revised full papers presented were carefully reviewed and selected from 72 submissions. The papers cover a broad range of topics related to all knowledge science-related areas including creativity support, decision science, knowledge science, data mining, machine learning, databases, statistics, knowledge acquisition, automatic scientific discovery, data/knowledge visualization, and knowledge-based systems.